Assessing the Effectiveness of the Problem-Based Learning (PBL) Model Across Study Programs on Students at Yogyakarta State University - Astuti, Vera; Purnamasari, Niken; Suyanto, Umar Yeni (Journal of Economics Education and Entrepreneurship, 2025)
Student learning outcomes are vital indicators of educational quality. and they continue to be a central focus in education systems worldwide. This study evaluates the effectiveness of the Problem-Based Learning (PBL) model in enhancing student outcomes at Yogyakarta State University. PBL engages students in solving real-world problems, promoting active learning and critical thinking. Using a Quasi-Experimental method with a One-Group Pre-test and Post-test design, the research examines PBL's impact on cognitive achievement in Economics Education, Management, and Office Administration Education programs. The findings reveal significant improvements in learning outcomes after PBL implementation, highlighting its potential to enhance educational quality across disciplines.